2016
DOI: 10.4062/biomolther.2016.030
|View full text |Cite
|
Sign up to set email alerts
|

Insulin as a Potent Stimulator of Akt, ERK and Inhibin-βE Signaling in Osteoblast-Like UMR-106 Cells

Abstract: Insulin is a peptide hormone of the endocrine pancreas and exerts a wide variety of physiological actions in insulin sensitive tissues, such as regulation of glucose homeostasis, cell growth, differentiation, learning and memory. However, the role of insulin in osteoblast cells remains to be fully characterized. In this study, we demonstrated that the insulin (100 nM) has the ability to stimulate the phosphorylation of protein kinase B (Akt/PKB) and extracellular signal-regulated kinase (ERK) and the levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The PCR protocol was as follows: initial denaturation at 95°C for 10 minutes followed by 40 cycles of 95°C for 30 seconds, 57°C for 30 seconds and 72°C for 30 seconds. The following PCR primer sets were used: Cofilin‐1 :5′‐GCCGCTATGCCCTCTA‐3′ (sense), 5′‐CAATTCATGCTTGATCCCT‐3′ (antisense) 12 ; Vimentin : 5′‐CCCTCACCTGTGAAGTGGAT‐3′ (sense), 5′‐GACGAGCCATTTCCTCCTTC‐3′ (antisense) 7 ; N‐cadherin : 5′‐GCCCCTCAAGTGTTACCTCAA‐3′ (sense), 5′‐AGCCGAGTGATGGTCCAATTT‐3′ (antisense) 13 ; Snail : 5′‐CAAGGAATACCTCAGCCTGG‐3′ (sense), 5′‐CATCTGAGTGGGTCTGGAGG‐3′ (antisense) 11 ; E‐cadherin : 5′‐GAACGCATTGCCACATACAC‐3′ (sense), 5′‐AGCACCTTCCATGACAGACC‐3′ (antisense) 7 ; ERK1 : 5′‐CGCTTCCGCCATGAGAATGTC‐3′ (sense), 5′‐CAGGTCAGTCTCCATCAGGTCCTG‐3′ (antisense) 14 ; ERK2 : 5′‐GAAGACACAGCACCTCAGCAA‐3′ (sense), 5′‐TGGAAGGCTTGAGGTCACGGT‐3′ (antisense) 15 ; GAPDH : 5′‐GTGAACCATGAGAAGTATGACAAC‐3′ (sense), 5′‐ATGAGTCCTTCCACGATACC‐3′ (antisense), 7 miR‐422a: 5′‐ GCTCCCATGCTATTAATATTCCTGGA −3′ (sense), 5′‐ CGATCGCGCTTCAGCTCA −3′ (antisense), 16 U6: 5′‐ GCTTCGGCAGCACATATACTAAAAT −3′ (sense), 5′‐ CGCTTCACGAATTTGCGTGTCAT −3′ (antisense) 17 . GAPDH was used as an internal control to normalize target gene expression.…”
Section: Methodsmentioning
confidence: 99%
“…The PCR protocol was as follows: initial denaturation at 95°C for 10 minutes followed by 40 cycles of 95°C for 30 seconds, 57°C for 30 seconds and 72°C for 30 seconds. The following PCR primer sets were used: Cofilin‐1 :5′‐GCCGCTATGCCCTCTA‐3′ (sense), 5′‐CAATTCATGCTTGATCCCT‐3′ (antisense) 12 ; Vimentin : 5′‐CCCTCACCTGTGAAGTGGAT‐3′ (sense), 5′‐GACGAGCCATTTCCTCCTTC‐3′ (antisense) 7 ; N‐cadherin : 5′‐GCCCCTCAAGTGTTACCTCAA‐3′ (sense), 5′‐AGCCGAGTGATGGTCCAATTT‐3′ (antisense) 13 ; Snail : 5′‐CAAGGAATACCTCAGCCTGG‐3′ (sense), 5′‐CATCTGAGTGGGTCTGGAGG‐3′ (antisense) 11 ; E‐cadherin : 5′‐GAACGCATTGCCACATACAC‐3′ (sense), 5′‐AGCACCTTCCATGACAGACC‐3′ (antisense) 7 ; ERK1 : 5′‐CGCTTCCGCCATGAGAATGTC‐3′ (sense), 5′‐CAGGTCAGTCTCCATCAGGTCCTG‐3′ (antisense) 14 ; ERK2 : 5′‐GAAGACACAGCACCTCAGCAA‐3′ (sense), 5′‐TGGAAGGCTTGAGGTCACGGT‐3′ (antisense) 15 ; GAPDH : 5′‐GTGAACCATGAGAAGTATGACAAC‐3′ (sense), 5′‐ATGAGTCCTTCCACGATACC‐3′ (antisense), 7 miR‐422a: 5′‐ GCTCCCATGCTATTAATATTCCTGGA −3′ (sense), 5′‐ CGATCGCGCTTCAGCTCA −3′ (antisense), 16 U6: 5′‐ GCTTCGGCAGCACATATACTAAAAT −3′ (sense), 5′‐ CGCTTCACGAATTTGCGTGTCAT −3′ (antisense) 17 . GAPDH was used as an internal control to normalize target gene expression.…”
Section: Methodsmentioning
confidence: 99%
“…But other growth factors present in serum such as cytokines might also be involved in this process. Previous studies have explored the role of insulin using osteoblast-like cells incubated in the absence of serum and confirmed that insulin was responsible for stimulating PI3K/Akt signaling cascade ( 44 , 45 ). Thus, elevated serum insulin level mediated by 1,25D in vivo study might be an explanation for the activation of PI3K/Akt signaling by 1,25D in hyperglycemia environment.…”
Section: Discussionmentioning
confidence: 91%
“…An analysis of cell cycle distribution in PDGF-treated osteoblasts using flow cytometry has revealed that PDGF treatment increased the number of cells in the S phase and decreased the cell numbers in the G0/G1 phase, indicating that PDGF promoted cell entry into the S phase in osteoblasts and inhibited cell apoptosis [ 52 ] being both ERK1 and ERK2 signaling pathways activated by PDGF [ 53 ]. Moreover, the ERK pathway has shown to be upregulated in response to insulin treatment in osteoblast-like cells providing that this growth factor is a potent stimulator in survival signaling pathways in insulin-sensitive cells [ 54 ].…”
Section: Discussionmentioning
confidence: 99%